(3GdJYdjbIs - (3HgGA GdOjf eMeO Hf EHQGgje Hf eMeO GdMdHj , GdeYQha HGHf GdfMGSs; (3GdYdhj , GdeXaQ Hf GdaVd Hf jMji GdMSjfj, CHh Ydj,J (B656 (3g` s
(3ChdgG (B:s
(3bGd GeQD GdbjS Hf MLQ Hf GdMGQK Hf COO hCe eQI eOdI , hgj ePML , hEfeG SejJ ePML , dCfgG hdOJ Ydi Cceg jbGd dgG ePML (B: (3baGfjc ef PcQi MHjH hefRd HSbW Gddhi Hjf GdONhd aMhed s
(3BNQgG (B:s
(3aJedG HjJfG CbWGQ hSefG hMSHc ef Zfi THY hQi s
(3hjdGMX Cf GdTQM HOhf ebOeIs
(3hWQjbJg Cf jCJi HeG ai GdHjJ ef GdZQjH Ke eG ajg ef GdeYfi hGdfMhs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B257 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B300 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B464s
Keywords: (3GdCOHs